Commit and Transmit: Molecular Players in Plasmodium Sexual Development and Zygote Differentiation. Issue 12 (December 2015) - Guttery, David S.; Roques, Magali; Holder, Anthony A.; Tewari, Rita
Abstract : During each cycle of asexual endomitotic division in erythrocytes, the malaria parasite makes a fundamental and crucial decision: to continue to invade and proliferate or to differentiate into gametocytes ready for continuation of sexual development. The proteins and regulatory pathways involved in Plasmodium sexual development have been of great interest in recent years as targets for blocking malaria transmission. However, the 'Holy Grail', the master switch orchestrating asexual-to-sexual commitment and further differentiation, has remained elusive – until now. Here we highlight the recent studies identifying the epigenetic and transcriptional master regulators of sexual commitment and discuss the key players in reversible phosphorylation pathways involved in sexual and zygote differentiation. Trends: Plasmodium sexual development starts in host erythrocytes with the formation of gametocytes (gametocytogenesis) that further differentiate to gametes; following fertilization, the zygote develops into an ookinete within the female mosquito vector. The apicomplexan-specific AP2-G transcription factor has been identified as a master switch for sexual commitment and gametocytogenesis. Two epigenetic regulators, HP1 and HDA2, control gametocytogenesis via AP2-G repression. Genome-wide functional screens of reversible phosphorylation have identified essential regulators of sexual development and differentiation.